Criteria Suggestive of Psychological Components of Itch and Somatoform Itch: Study of a Large Sample of Patients with Chronic Pruritus - Gudrun Schneider; Anna Grebe; Philipp Bruland; Gereon Heuft; Sonja Ständer (Medical Journals Sweden, 2020)
While psychological factors are relevant in many patients with chronic pruritus, not all patients can be offered psychologic, psychosomatic or psychiatric consultation. The aim of this exploratory study was to identify criteria suggestive of psychological factors relevant for the etiology of chronic pruritus and of somatoform pruritus. Routine data from the database of the Center for Chronic Pruritus of the University Hospital Münster were used, including the Neuroderm Questionnaire, Dermatology Life Quality Index and Hospital Anxiety and Depression Scale. Chronic pruritus patients (n = 3,391) without a psychiatric diagnosis in their medical history were compared to the 331 chronic pruritus patients with diagnoses of "psychological factors associated with etiology and course of chronic pruritus" (ICD-10:F54) or "somatoform pruritus" (F45.8) confirmed by an expert. The latter reported more pruritus triggers, especially "strain" and "emotional tension" and used more emotional adjectives to describe their pruritus. They reported more often scratching leading to excoriations, higher levels of pruritus, impairment of quality of life, anxiety and depression. These aspects suggest the presence of psychological factors in the etiology of chronic pruritus and somatoform pruritus. Prospective validation, however, needs to be carried out.